Anaerobic stabilized landfill leachate treatment using chemically activated sugarcane bagasse activated carbon: kinetic and equilibrium study. Issue 9 (19th February 2016) - Azmi, Nurshazwani Bt.; Bashir, Mohammed J.K.; Sethupathi, Sumathi; Ng, Choon Aun
Abstract: Adsorption via activated carbon (AC) is one of the best methods to treat stabilized landfill leachate. However, this technique has been justified due to expensive and limited resource of AC precursor. Thus, in this study, sugarcane bagasse, a cheap and abundant biomass from agricultural waste, was used to prepare AC. The prepared sugarcane bagasse activated carbon (SCAC) was tested for color, chemical oxygen demand (COD), and ammoniacal nitrogen (NH3 -N) removals from anaerobic stabilized landfill leachate. SCAC was prepared using physical and chemical activation. SCAC was characterized for its surface area, surface morphology, and functional groups. The performance of the adsorbent was examined in a batch mode study by varying the shaking speed, contact time, adsorbent dosage, and pH. The experimental results indicated that SCAC could adsorb and remove the pollutants from anaerobic municipal stabilized landfill. Removal of color, COD, and NH3 -N were favorably described by Langmuir isotherm model, with a maximum monolayer adsorption capacity of 555.56 Pt/Co, 126.58 and 14.62 mg/g, respectively. Pseudo-second-order model fits well with the experimental results and indicates that the adsorption was controlled by chemisorptions. The experimental results revealed that the optimum experimental conditions (e.g. 200 rpm shaking speed, 180 min contact time, 7 g AC dosage, and pH 7) resulted in 94.74, 83.61, and 46.65% removal of color, COD, and NH3 -N, respectively.